The Effect of Forging and Heat Treatment Variables on Microstructure and Mechanical Properties of a Re-Bearing Powder-Metallurgy Nickel Base Superalloy - Shamil Mukhtarov; Dmitry Karyagin; Artem Ganeev; Rishat Zainullin; Ruslan Shakhov; Valery Imayev (Metals, 2023)
In our previous works, the effects of forging and heat treatment variables on microstructure evolution and mechanical properties have been studied for an ingot-metallurgy Re-bearing nickel base superalloy. To overcome the issues associated with the production of large-scale ingots and fine-grained workpieces, in the present work, the effect of hot forging and heat treatment variables was studied in a Re-bearing nickel base superalloy prepared via powder metallurgy. The purpose of the study was to reach the properly balanced mechanical properties for the potential use of the superalloy as a disc material. The initial as-HIPed workpieces were subjected to different hot forging and post-forging heat treatment or only to heat treatment (no forging). For the processed workpieces, the recrystallization behavior, size, morphology and volume fraction of γ′ precipitates were evaluated by scanning electron microscopy followed by a study of mechanical properties. The most properly balanced mechanical properties (strength, ductility, creep resistance and creep rupture lifetime) were reached for the γ grain size of dγ ≈ 13.6 µm. A finer and coarser γ grain size (down to dγ ≈ 2.6 and up to dγ ≈ 37.5 µm) even when superimposed with a higher volume fraction of dispersed secondary γ′ precipitates (in the case of dγ = 27–37.5 µm) was associated with worse mechanical properties.